The Validity of Electronic Learning Materials Optical Instruments Based on Authentic Learning to Train Students' Problem Solving Skills - Fitriana Dewi Ramadhani; Mustika Wati; Misbah Misbah; Ketang Wiyono (Kasuari: Physics Education Journal (KPEJ), 2021)
Problem-solving skills are needed in solving various problems both academically and authentically. However, from the results of field studies, students' problem-solving skills are still relatively low. The authentic learning approach has received much scientific support to overcome this kind of problem. However, authentic learning-based teaching materials have not been widely developed, especially for high school physics learning. The specific purpose of this research is to describe the validity of the developed electronic teaching materials. This study uses the research design and development of the ASSURE model. Electronic teaching material validation data was obtained using a validation sheet. Validation is based on expert validation consisting of 1 practitioner and two academics. Validation data is expressed by the average value of the total score for each aspect of the assessment, and the calculation results are adjusted to the validity criteria. The results showed that: the validity of electronic teaching materials was categorized as valid with an average score of 3.90. It was concluded that authentic learning-based electronic teaching materials were declared valid and could be used as a stage for class trials on optical instrument materials